2021
DOI: 10.1155/2021/9945775
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Resistance Exercises plus Manual Therapy Is Effective in Improving Isometric Strength in Overhead Athletes with Shoulder Impingement Syndrome: A Randomized Controlled Trial

Abstract: Reduction in isometric strength of the scapulohumeral muscles is a commonly seen impairment in overhead athletes afflicted with shoulder impingement syndrome (SIS). The purpose of this study was to compare the effects of two different treatment programs: progressive resistance exercises plus manual therapy (PRE plus MT) and motor control exercises (MCE), on isometric strength of upper trapezius (UT), middle trapezius (MTr), lower trapezius (LT), serratus anterior (SA), supraspinatus (Supr.), anterior deltoid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 45 publications
(72 reference statements)
0
23
0
Order By: Relevance
“…4 More importantly, the majority of the included studies used more than 1 therapist for the delivery of the MT techniques, which could also have compromised the results. Finally, MT dosage was under-reported on many occasions 2,8,10,29,45,47 in terms of duration. As limited research exists on the optimal dosage of MT for shoulder pathology, research is necessary to establish the minimally effective dose of MT before examining its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 More importantly, the majority of the included studies used more than 1 therapist for the delivery of the MT techniques, which could also have compromised the results. Finally, MT dosage was under-reported on many occasions 2,8,10,29,45,47 in terms of duration. As limited research exists on the optimal dosage of MT for shoulder pathology, research is necessary to establish the minimally effective dose of MT before examining its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,18,22,28,54 Finally, 12 articles were found appropriate for a qualitative synthesis. 2,8,10,19,24,29,30,36,[45][46][47]55 After excluding 1 article 47 due to a lack of relevant data available in the full text and even after a request from the primary authors, the remaining 11 were found appropriate for quantitative synthesis. There was almost complete agreement between the 2 reviewers at the title/abstract screening stage (κ = 0.80) and at the full-text screening stage (κ = 0.82).…”
Section: Study Selectionmentioning
confidence: 99%
“…Finally, FRT7 is calculated by the sum of FRT4, FRT5 and FRT6. Active knee Range of Motion (ROM): represents how much the knee can bend and straighten on its own (no external force for the active method) (Gianola et al 2020 ; Sharma et al 2021 ). Isometric strength: measures the ability of the patient to hold a sustained contraction against a resistance for a specific duration.…”
Section: Resultsmentioning
confidence: 99%
“…Shoulder impingement syndrome comprises three distinct types: subacromial impingement, subcoracoid impingement, and internal impingement [12,14,15]. However, clinical understanding of shoulder impingement often remains limited, and these various forms of impingement are occasionally amalgamated and addressed as subacromial impingement.…”
Section: Discussionmentioning
confidence: 99%